Electroconductivity Profiles on Spray Drying: Feasibility Study on Reducing Fouling Deposit on Borosilicate Drying Chamber Surface via Alternating Repulsive Charges - Nur Arianna Arisya Nor Rashid; Saiful Irwan Zubairi; Nur Huda Faujan; Irman Abd. Rahman; Noraziani Zainal Abidin (Penerbit UTM Press, 2026)
Indexed by WOS / SCOPUS / MYCITE / ERA